Factors that protect against poor sleep quality in an adult lifespan sample of non-Hispanic Black and non-Hispanic White adults during COVID-19: A cross-sectional study - Hokett, Emily; Arunmozhi, Aditi; Campbell, Jessica; Duarte, Audrey (Frontiers in Psychology, 2022)
Stress in relation to the Coronavirus disease 19 pandemic (i.e., COVID-19, COVID stress) may be linked with poor sleep quality. The association between stress that is specific to the COVID-19 pandemic and sleep quality has been understudied, particularly in racially diverse people across the adult lifespan. Here, we investigated self-reported sleep quality in relation to COVID stress and factors that may protect against experiencing poor sleep quality from high COVID stress, including social support and religiosity. We recruited non-Hispanic Black (n=73) and non-Hispanic White (n=178) participants across the adult lifespan (18-76 years) using an online, cross-sectional design during the COVID-19 pandemic (March 2021-June 2021). We asked participants to report information regarding demographics (age, race/ethnicity, years of education), sleep (sleep quality, sleep habits), and positive (social support, religious activities) and negative (events of discrimination, depression, general stress, COVID stress) psychosocial factors. Across age and racial groups, better sleep habits were associated with better sleep quality, and higher COVID stress was linked to poorer sleep quality. Black participants reported higher quality sleep than White participants (p = .006). They also endorsed greater private and internal religiosity (p’s < .001). Across racial groups, moderation analyses revealed a protective effect of religiosity against poor sleep (p’s < .006). Specifically, individuals with high religious activity and high COVID stress did not experience poor sleep quality, but individuals with low religious activity and high COVID stress demonstrated poor sleep quality. These results remained significant when controlling for general stress. Protective factors, such as religiosity, may mitigate the negative associations between high COVID stress and poor sleep quality.